Dancing with Legitimacy: Globalisation, Educational Decentralisation, and the State in Indonesia - irsyad zamzani (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2020)
Decentralization has become a global norm that has changed the face of education governance in many countries since the late 1970s. This movement utterly swept up Indonesia in 2001 after the severe legitimacy crisis ended the three-decade-reigning centralist regime of the New Order. Using the analytical concepts of the new institutional theory and drawing upon data from documents and interviews with strategic informants, the thesis investigates how the institutional legitimacy of educational decentralization was garnered, manipulated, and then contested. The narrative of educational decentralization in Indonesia was initially scripted by multilateral actors with the neoliberal spirit of market supremacy. However, against the liberal and critical arguments that suggest the weakening of the central state or the rise of market institutions as the follow-up of educational decentralization, the findings show a somewhat contrasting reality. Decentralization has facilitated the proliferation of Weberian states in the local district arenas, which equally claim institutional legitimacy for governing the local educational system in their respective ways. From the comparative studies of two local district governments, Kupang and Surabaya, the thesis shows how the legitimacy of the central government authority continues to be challenged in the localities. Despite the central government’s pressures for national standards and their enforcement measures, local educational governance survives with different, illegitimate models and practices. Thus, rather than becoming a local 94 | Masyarakat Indonesia, Vol. 46 (1), JUNI 2020 INTRODUCTION Indonesia is one of the countries deeply affected by the global decentralisation movement. There had been several efforts by the country’s government to cope with such global pressure (Devas, 1997; Malo and Nas, 1991), but none had much effect until the 2001 decentralisation big bang (Bünte, 2004; Fealy and Aspinall, 2003). The post-2001 decentralisation was one of the major institutional reforms that ended the dictatorial Suharto’s New Order regime in the late 1990s. Before the reform, Indonesia education was highly centralised and fragmented. The management of education was shared between the Ministry of Education and Culture (MoEC) and the Ministry of Home Affairs (MoHA). The MoEC was responsible for the curriculum of all primary and secondary schools and the personnel of secondary schools: the MoHA was responsible for the personnel of primary and junior secondary schools. Both departments had their provincial and district or municipal offices and this made management highly bureaucratic. The 2001 decentralisation reform dissolved both departments’ organisational structures in the regions, which gave the district and municipal governments greater autonomy in running most public service sectors, including education. Adopting common decentralisation practices, some policy reforms were also enacted to give schools a degree of managerial autonomy and to provide the community with a participatory role in policymaking. Governance fragmentation and inefficiency were the problems that most concerned Indonesian reformers when they firstly discussed and formulated the reform program (Jalal and Supriadi, 2001). By removing the central government’s bureaucratic structure from local bureaucracies, it was expected that education delivery would become more efficient and the district government the only education authority in the regions (World Bank, 1998a). However, this has never been the case. On the one hand, decentralisation was welcomed by local élites as a big increase in power and authority. They do become dominant education authorities which control all public schools and teachers in their territories. On the other hand, despite the central-government structure’s removal, education decentralisation reform did not significantly reduce the MoEC’s influence. Two years after decentralisation, in 2003, a new education law was passed and the MoEC was given a new role: that is, setting the national education standards. With these standards, the ministry is authorised to inspect school performance through the school accreditation, student performance through the national examinations, and teacher performance through the teacher certification policy. In addition, to ensure those standards were maintained, the central government started to regulate almost all facets of education: from curriculum to school uniforms. There are hundreds of ministerial regulations and trillions of rupiah allocated from the central government budget to support the implementation of the standards. This makes the structure of Indonesian education governance so contradictory: it is radically decentralised but at the same time highly standardised. The demands of decentralisation and standardisation have become increasingly stronger from the two competing parties: the local and central governments. The MoEC keeps producing and revising regulations and policy strategies to enforce the standards only to find that they are too often neglected by the local governments. Many of the MoEC’s regulations of things like school fees, principals’ appointment, teacher management and classroom size were evaded because they were at odds with local interests. This practice has frustrated MoEC officials who frequently express their bitterness. They are helpless to deal with all the local noncompliance because the MoEC no longer has the power to apply basis for reinforcing the legitimating capacity of educational decentralization as a global institution, the different practices might become the local source of delegitimation. Some nation-states would rethink their conformity to the international pressure of decentralization if they were aware that the policy would potentially lead them to another crisis of legitimacy